Bioenergy from anaerobic degradation of lipids in palm oil mill effluent - Anwar, Ahmad; Ghufran, Rumana; Zularisam, A. W. (Springer Netherlands, 2011)
Fossil fuels are the lifeblood of our society and for many others around the world. The environmental pollution due to the use of fossil fuels as well as their gradual depletion make it necessary to find alternative energy and chemical sources that are environmentally friendly and renewable. Palm oil mill effluent (POME), a strong wastewater from palm oil mills, has been identified as a potential source to generate renewable bioenergies through anaerobic digestion. Thus, it has received considerable attention as feedstock for producing various value added products such as methane gas, bio-plastic, organic acids, bio-compost, activated carbon, and animal feedstock. Lipids are one of the major organic pollutants in POME. Furthermore, waste lipids are ideal potential substrates for biogas production, since theoretically more methane can be produced, when compared with proteins or carbohydrates. The objective of this review paper is to disscuss the microbial communities involved in the anaerobic degradation of long chain fatty acid and bioenergies and by-products from POME. With these options (Renewable and sustainable bioenergies) we can help phase out our dependency on fossil fuels and find clean, efficient, sources of power.